Impact of omnichannel integration on Millennials' purchase intention for fashion retailer - Teerada Cattapan; Siwarit Pongsakornrungsilp (Cogent Business & Management, 2022)
The COVID-19 pandemic has hastened the expansion of omnichannel purchasing globally including in Thailand. This quantitative study employs the stimulus-organism-response (S-O-R) framework to investigate the impact of channel integration on increasing customer satisfaction or reducing perceived risk, which leads to increased purchase intention for fashion products. Using an online questionnaire, data were collected from 400 Thai Millennials (aged 22-40~years) interested in buying luxury fashion products. The data were analysed using structural equation modelling. The results showed that integrated product and price, integrated promotion, and integrated information access influenced customer-perceived risk reduction, and integrated product and price, integrated promotion, integrated transaction information, integrated information access, and integrated customer service influenced customer satisfaction. In addition, perceived risk is related to customer satisfaction and purchase intention. These findings provide both theoretical and managerial implications for omnichannel retailers in developing their marketing strategies.
Keywords: 650; channel integration; fashion retailer; Millennials; omnichannel; purchase intention